Impact of AlN-SiC Nanoparticle Reinforcement on the Mechanical Behavior of Al 6061-Based Hybrid Composite Developed by the Stir Casting Route - S. Kaliappan; A. Shanmugam; Pradeep Johnson; M. Karthick; S. Sekar; Pravin P. Patil; M. K. S. Sai; K. P. Yuvaraj; Venkatesan Govindaraajan (Advances in Materials Science and Engineering)
The enhancement of composites’ mechanical characteristics (tensile, compressive, and hardness) is a constant demand for technological advancement. The stir casting process is used to make the hybrid aluminium alloy metal matrix composites Al 6061-SiC-AlN in our present study. To create mechanical qualities such as tensile, compressive, and hardness, silicon carbide and aluminium nitride (both 3% and 6%) were utilized as the reinforcement. The tensile strength, compressive strength, and hardness of the Al 6061-SiC-AlN hybrid composites samples were determined. The tensile, compressive, and hardness parameters of Al 6061-SiC-AlN hybrid composites are estimated and evaluated to those of the matrix Al 6061 alloy. With the inclusion of silicon carbide and AlN nanoparticles, the tensile strength, compressive strength, and hardness increased from 328 to 385 MPa, 145 to 178 Mpa, and 302 to 724 VHN, respectively.